Alternative theorizing of multicultural education: an Islamic perspective on interculturality and social justice. Issue 2 (5th July 2021) - R'boul, Hamza
Abstract : Purpose: This paper aims to discuss the possibility of embracing an Islamic perspective on interculturality and social justice as an underlying system of multicultural education. While western thought continues to dominate the education scholarship, advancing an alternative epistemology can ameliorate the scope of multicultural education by considering other relevant elements. In particular, interreligious relations have not been researched extensively in terms of managing cultural capital in schools. This paper argues that Islamic ethics provide a system of justice and rules of conduct that satisfy the principles of multicultural education. Design/methodology/approach: Classical texts (Qu'ran and Hadith) are analyzed to explore the Islamic perspective on interculturality and social justice. While the plurality of interpretations is remarkable, the aim is to examine these texts on the basis of ethical and humanistic orientation. Findings: Islamic ethics are commensurate with intercultural empathy and multicultural education. While some verses are interpreted as evidence of the religious legitimacy of enmity and hostility towards non-Muslims, they are decontextualized readings isolated from the verses' historical contexts. Practical implications: This paper proposes considering Islamic ethics as a foundation of multicultural education. Because Islam promotes social justice, teachers and students are encouraged to take action and never tolerate any act of oppression. Teachers should pay attention to conflicts that may arise from theological differences among students. Originality/value: This paper offers a new perspective that has been sidelined and not considered in Modern issues. Because multicultural education recognizes the necessity of appreciating all cultures, Islam delivers a similar framework that is based on peaceful intercultural communication and social justice.